Research on the development of nanocellulose based on agricultural waste and its processing and utilization in food sausages - Yongjie Ma; Hongliang Bao; Ziqi Mai; Jingyi Wei; Xiaobing Guo; Wenbin Dong (CyTA - Journal of Food, 2025)
Pepper cultivation generates over 50 million tons of straw waste annually, with a global utilization rate below 20%. To address this resource inefficiency and explore sustainable food additives, cellulose was extracted from discarded pepper stems (PS) (15–34.5% yield) via nitric acid – ethanol treatment, followed by nanocellulose synthesis through sulfuric acid hydrolysis (36.13% average yield). Characterization of nanocellulose was analyzed using scanning electron microscopy, Fourier-transform infrared, and X-ray diffraction analysis. It was found through mice experiments that intaking nanocellulose-containing sausages could significantly reduce the food intake of mice, inhibit the weight growth of mice, and significantly improve the strength of the skeletal muscles of mice. This research provides a basis for subsequent studies on the efficient recycling of PS and the application of nanocellulose as a food additive in food processing.